Does Peso Depreciation or More Government Debt Affect Aggregate Output? The Case of Chile - Hsing, Yu; Phillips, Antoinette S; Phillips, Carl; Morgan, Yun-Chen (Asian Journal of Economics and Empirical Research, 2019)
This paper attempts to determine whether real peso depreciation/appreciation or fiscal expansion would be effective in raising output in Chile. Real peso depreciation tends to stimulate exports but raise import costs and domestic inflation. More government debt-financed spending tends to increase aggregate demand but cause the crowding-out effect. Based on an extended IS-MP-AS model (Romer, 2000) incorporating the monetary policy function and the advanced EGARCH process, this study shows that real peso appreciation increased output during 2006.Q1-2011.Q3 whereas real peso depreciation raised output during 2011.Q4-2016.Q4 and that a higher lagged government debt ratio raised output. In addition, a lower U.S. real interest rate, real crude oil price or expected inflation helped increase output. Hence, real peso depreciation or appreciation may increase or reduce output depending upon the development phase, and expansionary fiscal policy is effective. Although more government debt-to-GDP ratio has a positive effect on output, fiscal discipline needs to be pursued as the effect of debt-financed government spending seemed to be leveling off in recent years.